APLIKASI INFORMASI NEGARA ASEAN PADA SMARTPHONE BERBASIS ANDROID MENGGUNAKAN PHONEGAP - SRI MELATI SAGITA (Faktor Exacta, 2016)
With the growing age and technology advances, easey of access to information is one of the important needs in the communit such as mobile phone and can be used not only to call and send text messages, but also can help daily activities. This led to many mobile phone manufacturers compete by making the operating system used on mobile phones (cell phones), among others, Blackberry OS, Symbian OS, iOS, Linux, and Android. Android was developed by Google, and is used by some vendors that make mobile smartphones like Samsung, Sony, LG, HTC, etc. Lately Android is not only built using the Java language, but the language of HTML, Java Script and CSS. But it was not easy to do if only the Java language using the facilities provided. Hence comes the tool to connect the HTML files, Java Script and CSS to Java Android is PhoneGap. Application information introduction of the ASEAN member countries is built with several stages. Starting with designing UML Use Case Diagrams, Activity Diagrams, Sequence Diagrams and Class Diagrams. Then proceed with designing the look, and build a program with program coding on ADT Bundle and Adobe Dreamweaver. Once it is done compiling and then implemented using the emulator and smartphones Galaxy Smartfren Andromax U. Keywords: Information of ASEAN countries, Android, PhoneGap